Microbiological and urinalysis assessment of UTIs in COVID-19 patients at Dr. Zainoel Abidin Hospital, Banda Aceh. - MAHDANI, WILDA; ZIKRI, MUHAMMAD SHADIQUL; SAMINAN, SAMINAN (Universitas Syiah Kuala, 2025)
One of the secondary infections observed among COVID-19 patients is a Urinary Tract Infection (UTI). The presence of bacteria and fungi causes UTI, which can certainly occur after a urine culture. Urinalysis is one of the critical examinations to diagnose UTIs and assess functional disorders in the urinary tract. This study examines the characteristics of microbes isolated from urine specimens and urinalysis results in COVID-19 patients at Dr. Zainoel Abidin Hospital, Banda Aceh. This observational analytic study used secondary data from urine culture and urinalysis results of COVID-19 patients by implementing the total sampling technique. This study involved 110 urine culture data from confirmed COVID-19 patients. Comparative analysis of parameters between positive and negative urine culture groups with urinalysis results using categorical variables through the Chi-square test and Fisher's Exact test. The findings suggest that Escherichia coli, Enterococcus spp., and Candida spp. are the predominant uropathogens in COVID-19 patients, with urinalysis frequently indicating leukocytosis as a marker of urinary tract involvement. Urine culture is the gold standard for quantitatively diagnosing UTIs by determining bacterial density and identifying specific pathogens. Urinalysis, which checks for leukocytes in the urine, can support these results.